Comparison of shear bond strength of two veneering ceramics to zirconia - Mansour Rismanchian; Soufia Shafiei; Navid Askari; Niloufar Khodaeian (Wolters Kluwer Medknow Publications, 2012)
Background : Chip-off fracture of veneering porcelain has been described as the most frequent reason for the failure of zirconia-based fixed partial dentures. The purpose of this study was to evaluate the shear bond strength (SBS) of two commercial zirconia core ceramics to their corresponding veneering ceramics. Materials and Methods : Zirconia disks with 7-mm diameter and 3-mm height were prepared (Cercon and Biodenta systems) and veneered with recommended layering ceramics (Cercon ceram and 2 in 1 ceramic, respectively) (n = 10). The disks were polished with diamond paste and airborne-particle abraded before layering. The specimens were mounted in a T-shaped metal holder using autopolymerized acrylic resin and stored in 37΀C distilled water for one week, after which they were subjected to thermal cycling. SBS of zirconia core to veneering ceramic was measured using a universal testing machine and failure modes were determined microscopically. Data were analyzed using t test (α < 0.05). Results : Mean (΁SD) SBS values were 27.19(΁3.43) and 28.22(΁4.08) MPa for Cercon and Biodenta systems, respectively, with no significant difference. Biodenta system showed more adhesive failure compared to more combined (adhesive and cohesive) failures in Cercon system. Conclusion: Within the limitations of this study it can be concluded that SBS of Biodenta and Cercon specimens were nearly the same, but the fracture mode of these two systems were different. Since Biodenta fracture pattern was predominantly adhesive, it seems that maybe Biodenta porcelain was stronger than Cercon porcelain where as its adhesive bond was weaker.